An empirical study on the efficiency of the Singapore equity market. - Koh, Wai Khuen. (2008)
This paper aims to determine the efficiency of the Singapore stock market empirically, using conventional least-squared regression as well as more sophisticated testing techniques such as Vector Autoregression (VAR) andvariance bounds tests. The results will provide much insight into the development of the equity market in light of Singapore’s efforts to become a global financial hub.